2016
DOI: 10.1590/1414-431x20155036
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits and psychiatric comorbidities in alcohol dependence

Abstract: Non-adaptive personality traits may constitute risk factors for development of psychiatric disorders such as depression and anxiety. We aim to evaluate associations and the predictive value of personality traits among alcohol-dependent individuals, with or without psychiatric comorbidities. The convenience sample comprised two groups of males over 18 years of age: one with subjects who had an alcohol dependence diagnosis (AG, n=110), and a control group without abuse and/or alcohol dependence diagnosis (CG, n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…Physical adverse effects include hepatic cirrhosis, neoplasia, gastritis, esophageal varices, pancreatitis, and diabetes mellitus, among others. Psychiatric effects include elevated rates of mood and/or anxiety disorder co morbidities, which is associated with difficulty in adhering to treatment and worse prognoses [1][2][3]. Alcohol use disorders (AUDs) are responsible for 5 million deaths per year [4].…”
Section: Introductionmentioning
confidence: 99%
“…Physical adverse effects include hepatic cirrhosis, neoplasia, gastritis, esophageal varices, pancreatitis, and diabetes mellitus, among others. Psychiatric effects include elevated rates of mood and/or anxiety disorder co morbidities, which is associated with difficulty in adhering to treatment and worse prognoses [1][2][3]. Alcohol use disorders (AUDs) are responsible for 5 million deaths per year [4].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, alcohol preferring (AA) rats may exhibit depressive-like characteristics following voluntary alcohol intake compared to alcohol non-preferring (ANA) rats (Viglinskaya et al 1995). Although various theories have attempted to explain the association between AUD and depression, it appears that a number of factors, including genetic predisposition and alterations in neurochemical substrates, such as the noradrenergic system, may contribute to this co-morbidity (Balsamo et al, 2016; Bravo et al, 2017; Donadon and Osorio, 2016; Getachew et al, 2010; Jung et al, 2016; Kalejaye et al, 2013; Merikangas and Gelernter, 1990; Ovestreet et al, 2005; Rezvani et al, 2002, 2007; Rincon-Hoyos, et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…[1] Studies have shown that out of two billion alcohol users worldwide 76.3 million (7.63%) have at least one additional disorder caused by their habit. [2,3,4] Alcohol use disorders can also mimic or potentiate most other psychopathological symptoms. [5] There has been an increase in the incidence of dual diagnosis in recent years.…”
mentioning
confidence: 99%